A PORTRAIT OF TEACHER TALK IN EFL CLASSROOM INTERACTION A case study at the first grade of a senior high school in Pekanbaru - Fauziah, Armiati (2011)
This study aims to investigate teacher's talk in EFL classroom interaction in a senior high school. Three major problems posed in this study concern (I) portrait of teacher talk in EFL classroom interaction, (2) the problems faced by the teacher in developing classroom interaction, and (3) the ways the teacher solves the problems. This study applied a qualitative study which employed a descriptive method with multi instruments. The data were obtained from classroom observation, videotaping, audio taping, and interview. The observation was done in the classroom for 5 meetings. One English teacher and a class of first year student were involved as participants of this study. The interview with the teacher and five students was done to find the problems that occurred in EFL class and the ways to solve them. In data analysis, parts of classroom interaction which contain teacher talk were identified as teaching behaviors. Each of the teaching behaviors was identified based on Foreign Language Interaction analysis (FLINT System adopted from Moskowitz,1971). Data gathered from the interviews and observations were all transcribed, and the data from observation was analyzed by employing classroom interaction analysis. The data obtained from interview was analyzed based on the data reduction and interpretation. The data analysis was carried out through sorting out similar information, categorizing the information, and interpreting the data. The categorization will be based on data obtained. Then the information was described based on FLINT system. The data were compared, contrasted, and interpreted afterwards to answer the research questions. For the first research problem, this study identifies how the teacher develop classroom interaction in delivering material by using FLINT. In this regard , the teacher talk in delivering material is identified, and categorized and descriptive quantification was used to see trends in teacher talk in EFL class. For the second research problem, this study identifies that teachers' problems in developing interaction in EFL class include mixed abilities students, large classes, seating arrangement, and teacher voice. For the last research problem, the finding reveals that teacher solve her problem in developing interaction in EFL Class by doing individual approach and asking the simple questions or giving the simple tasks to the low achievement students. To solve the problem of large class, the teacher made the variation of methods, techniques and activities which enable the students to interact in the classroom. The teacher could do nothing with seating arrangement due to the small size of the classroom. Dealing with her soft voice, the teacher has tried to make her voice louder. Speaking slower is a way taken by the teacher to solve the problem of speaking fast. Finally, the teacher is recommended to give the same chance to all students to interact in the classroom. In addition, she must also train herself to speak- slower ad louder for effective interaction in delivering the lesson.